Analisis Gaya Komunikasi Calon Presiden dalam Menanggapi Isu Menjelang Pemilihan Presiden 2019 - Muhammad Ilham (Program of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2020)
Facing the 2019 presidential election contestation of the Republic of Indonesia, competing presidential candidates face a variety of things, especially issues that develop ahead of the presidential election. This issue, which was packaged in the mainstream media, social media and online media, has had an extraordinary influence on the electability and image of the candidate. Various issues that have drawn attention are more concerned with issues of background, ideology, ideology and even to personal problems, which are very draining the energy of the presidential candidate to look for loopholes to refute, confirm or give an open statement to clarify the matter.In this study, an analysis was conducted based on the characteristics of critical discourse analysis through action, context, history of power and ideology to gain knowledge about the communication styles of presidential candidates in responding to issues leading up to the presidential election. The results show that the communication style of presidential candidate Joko Widodo is more directed to the systematic style while presidential candidate Prabowo Subianto is more spirited style.